Gold & water : a history of Sofala and the Turon goldfield - Higgins, Matthew, 1957- (Bathurst, N.S.W. : Robstar : distributed by Timothy Carter Public Relations, 1990)
Annotation Pending.
Includes index.
Bibliography: p. 134-138.
Keywords: Gold mines and mining -- New South Wales -- Turon River Region -- History; Race relations - Violent - Massacres, murders, poisonings etc. - To 1900.; Settlement and contacts - Colonisation; Settlement and contacts - Explorers - Aboriginal guides; Wiradjuri people (D10) (NSW SI55-07); Sofala (N.S.W.) -- History; Sofala (SW NSW SI55-08); Bells Falls (SW NSW SI55-08)